Técnicas de co-design aplicadas ao desenvolvimento de uma interface USB - Souza, Jonathan Toczek (2006)
This dissertation is a study about hardware/software co-design, motivated by the increasing complexity on the development of embedded systems and the emergence of the System-on-Chip (SoC) technology. Considering this context, the work presented here proposes a methodology that provides a high level of abstraction, allowing the designers: a better management of the complexity, a well defined visualization of the development process and a smooth refinement. Thus the project decisions, hardware/software partition and trade-off can be simplified in an easy and natural way. With this objective, it was used the unified modeling language - UML, for the high level system specification, and the SystemC language, for the creation of executable prototypes and simulation of the different models defined by the proposal. In order to demonstrate the methodology, the implementation of an USB (Universal Serial Bus) interface will be specified and refined smoothly. The USB has co-design characteristics, which justifies its use as a test case. In this way, considering the large production demand and the short life time of these modern systems, currently found in almost all places of our daily life, like: cars, cellular phones, televisions, microwaves and others; this dissertation contributes for methodological efforts toward a rising on the productivity upon these complex systems development.